KARAKTERISASI KUALITAS BUAH EMPAT GENOTIP PEPAYA (Carica papaya L.) KOLEKSI BALAI PENELITIAN TANAMAN BUAH TROPIKA - Dewi Fatria; Noflindawati Noflindawati (Jurnal Floratek, 2014)
The research was conducted at Post Harvest Laboratory of Indonesian Tropical Fruit Research Institute (ITFRI) from March to May 2010. The design used was a randomized complete block design with 4 replicates. Papaya genotypes tested were  BT-01, BT-02, BT-03, and BT-04. The results showed that papaya genotypes of  BT-01, BT-02, BT-03, and BT-04 were not significantly different each other on physical fruit characters i.e. fruit length, fruit width, fruit weight, and stem length.  However, the thinnest fruit flesh was found at BT-3 genotype and the thicknest flesh was at BT-2 genotype. The lowest fruit cavity was found at genotype BT-1 and the highest was at the BT-2.  The lowest hardness of fruit skin and flesh  was found at genotype BT-4 and the highest hardness of skin was at BT-3,  while the highest hardness of flesh was at BT-1 and BT-2.  Chemical quality of total dissolved solid, vitamin C, acid content, and water content was not significantly different among the four genotypes BT-1, BT-2, BT-3, and BT 4.